More active, less aggressive! Understanding how physical activity reduces aggressive behavior among Chinese adolescents: a three-wave mediation model - Yue, Xiuzhuan; Cao, Haiying; Wang, Xueying; Zhu, Dong; Hu, Chang (Frontiers in Psychology, 2025)
BackgroundAdolescent aggression is a pressing global concern, especially in school contexts. Although prior studies suggest an inverse association between physical activity and aggression, longitudinal evidence on the mediating role of self-control remains limited. This study addresses this gap by testing a three-wave longitudinal mediation model, examining whether physical activity predicts reduced aggression through enhanced self-control, and whether these pathways are moderated by gender and grade.MethodsThis one-year longitudinal cohort followed Chinese adolescents across three waves. At baseline (T1), 2,011 students were enrolled; 1,927 and 1,866 participants completed the second (T2) and third (T3) assessments, respectively. Physical activity was captured with a single-item measure, self-control with the Brief Self-Control Scale (BSCS), and aggression with the Buss–Perry Aggression Questionnaire (BPAQ). Gender, grade, and baseline aggression were included as covariates. Analyses were conducted in SPSS 26; mediation was tested using the PROCESS macro (Model 4). To evaluate moderation by gender and grade, multi-group structural equation models were estimated in AMOS 28.0.ResultsPhysical activity at T1 was significantly and negatively associated with aggressive behavior at T3 (β = −0.083, p < 0.001). Self-control at T2 partially mediated this relationship (mediation effect = −0.035, 95% CI [−0.046, −0.025]), indicating that increased physical activity enhances self-control, which in turn reduces aggressive behavior. Multi-group analyses revealed that the effect of self-control on aggressive behavior was stronger in girls. In comparison, the effect of physical activity on self-control was stronger in Grade 7 students.ConclusionThis study presents longitudinal evidence demonstrating that enhanced self-control, developed through physical activity, leads to a reduction in aggressive behavior among adolescents, with variations observed based on gender and grade level. The results emphasize the significance of incorporating physical activity into school-based programs aimed at improving mental health and mitigating aggression in adolescents. To strengthen these findings, future research should investigate other potential mediating factors and utilize experimental methodologies.